PROGRAM KEMITRAAN MASYARAKAT PELATIHAN IN LITERASI DAN SAINS DI SMKS BINTANG PERSADA DENPASAR - Dewa Ayu Widiasri; Gusti Ayu Rai; I Made Darmada; Ni Made Pira Erawati (Jurnal Pengabdian Kepada Masyarakat Widya Mahadi, 2024)
Literacy and science are part of the National Literacy Movement launched by the government which encourages people to be able to think scientifically. The aim of this activity is to train teachers regarding literacy and science knowledge to improve the ability to answer PISA questions for children aged 15-16 years. The implementation method is through socialization, training and mentoring activities using technology and follow-up. The results of data analysis show that the PISA scientific literacy scores of Indonesian students are low and have never reached the standard scores set by PISA. Factors causing the low scientific literacy of Indonesian students are students' misconceptions about science, teachers not mastering scientific literacy, and infrastructure. In everyday life, the application of literacy and science is very broad. Science is a way to obtain new knowledge in the form of scientific products and scientific attitudes through an activity called the scientific process. Based on the results of the PkM activities, it was found that all participants in the literacy and science training activities were very enthusiastic, enthusiastic and had high motivation in participating in the training. Participants had an increase in science planning as seen from the literacy and science material. Teachers can now create literacy and science questions based on the characteristics of the Minimum Competency Assessment (AKM) in accordance with the PISA test questions for children aged 15-16 years.